The Role of Living Wage Perception in Enhancing Employee Dignity at Work in the Hospitality Sector - Dhungana, Madan; D.C., Samikshya (Journal of Emerging Management Studies, 2026)
Purpose – This study investigates the perception of a living wage on hospitality employees’ recognition and dignity at work, by considering the relationship between wage moderation and responsible consumption, wage sufficiency, workplace respect and treatment and employee dignity at work. Design/methodology/approach – A quantitative cross-sectional research design with primary data collection was used employing a structured questionnaire with 206 hospitality employees in Nepal. The study utilized descriptive statistics, correlation analysis, and multiple regression analysis techniques to investigate the relationship between variables and test hypotheses. Findings – The results show that Living Wage Sufficiency (β = 0.174), Wage Moderation and Responsible Consumption (β = 0.325), and Workplace Respect and Treatment (β = 0.453) significantly impact Recognition and Dignity at Work. Workplace Respect and Treatment is identified as the strongest predictor, contributing to a model that explains 77.9% of the variance in employee dignity. A strong positive correlation (r = 0.838) exists between Workplace Respect and Treatment and Recognition and Dignity at Work. Conclusion – Employee dignity and recognition in hospitality are strongly enhanced when workplaces combine respectful treatment with fair, sufficient, and responsibly managed wage conditions. While workplace respect is the most influential factor, wage sufficiency and moderation remain essential and independent contributors to employees’ sense of value and dignity at work. Implications – The study has several important theoretical as well as practical implications. Theoretically, the study extends the Kantian dignity and attitude theories by providing empirical validation of the multidimensionality of workplace dignity in a developing country context. Practically, it highlights the importance for hospitality organizations to create a respectful workplace culture in addition to maintaining fair, adequate, and transparent wage-related practices to enhance employee dignity and recognition.